Facilitating Children's Ability to Distinguish Symbols for Emotions: The Effects of Background Color Cues and Spatial Arrangement of Symbols on Accuracy and Speed of Search. - Wilkinson, Krista M.; Snell, Julie (American Journal of Speech-Language Pathology, 2011)
Purpose: Communication about feelings is a core element of human interaction. Aided augmentative and alternative communication systems must therefore include symbols representing these concepts. The symbols must be readily distinguishable in order for users to communicate effectively. However, emotions are represented within most systems by schematic faces in which subtle distinctions are difficult to represent. We examined whether background color cuing and spatial arrangement might help children identify symbols for different emotions. Method: Thirty nondisabled children searched for symbols representing emotions within an 8-choice array. On some trials, a color cue signaled the valence of the emotion (positive vs. negative). Additionally, the symbols were either (a) organized with the negatively valenced symbols at the top and the positive symbols on the bottom of the display or (b) distributed randomly throughout. Dependent variables were accuracy and speed of responses. Results: The speed with which children could locate a target was significantly faster for displays in which symbols were clustered by valence, but only when the symbols had white backgrounds. Addition of a background color cue did not facilitate responses. Conclusions: Rapid search was facilitated by a spatial organization cue, but not by the addition of background color. Further examination of the situations in which color cues may be useful is warranted.